Toward A Fiscal Union for the Euro Area - Allard, Celine (Staff Discussion Notes; Staff Discussion Notes, 2013)
This is on a highly topical issue and addresses a key policy issue for Europe-namely, reinforcing EMU institutional architecture along with the Banking Union. Some proposals have emerged in Europe, and it will be important to put out staff views on this issue. In that context, publication as an SDN is appropriate, given the high profile nature and relevance of the topic-much like the Banking Union paper done a few months ago.